Differences in Work Values and Work Attitudes of Generations X and Y in Malang City - Melyani Melyani; Peter Remy Yosy Pasla (Jurnal Ilmu Manajemen Profitability, 2024)
The working generation of people in Indonesia has now moved to the next generation, namely Generation X and Generation Y. With the difference between the two generations, several previous researchers stated that there were differences in work attitudes and work values of employees of different generations. However, there are studies from previous studies which state that there is no difference. Therefore, this study aims to determine whether there are differences in work values and work attitudes of generations X and Y in Malang City. The type of research used is comparative quantitative research. The population of the study is the workforce in Malang City in 2020, while the sample used is 400 employees consisting of 288 Generation X and 112 Generation Y. Based on a series of Independent Sample T-Test and Multiple linear regression test found significant differences in work values and work attitudes in Generations X and Y in Malang City, where these differences were analyzed based on the factors forming work values and work attitudes